Comparison of balance performances of athletes from different sports branches - Ali Tatlıcı (Türk Spor ve Egzersiz Dergisi)
This study aimed to investigate the comparison of the dynamic balance performances of basketball and football players. Ten male basketball players (age 17,60±0,69 years, height 1,90±0,04 cm, body weight 87.80±9.19 kg) and ten male football players (age 17,50±0,97 years, height 1,78±0,04 cm, body weight 74,50±12,04 kg) voluntarily participated in the study. Both groups’s athletes continue to train actively in their sports clubs. Biodex Balance System (BBS, Biodex Medical Systems Inc., Shirley, NY) was used to test dynamic balance, and three index scores were recorded as an overall stability index (OSI), an anterior-posterior stability index (APSI), and a medial-lateral stability index (MLSI). Mann Whitney U Test, non-parametric tests, was used to compare both groups and the significance level was set at p lt; 0.05. Results. There were no significant differences between groups in terms of OSI and APSI but MLSI was significantly different in favor of the football group (p lt;0.05). It can be concluded that football players can exhibit better dynamic balance than basketball players.